Hydrated alkali-B11H14 salts as potential solid-state electrolytes - Souza, Diego; Møller, Kasper; Moggach, S.A.; Humphries, Terry; D'Angelo, A.M.; Buckley, Craig; Paskevicius, Mark (ROYAL SOC CHEMISTRY, 2021)
Metal boron-hydrogen compounds are considered as promising solid electrolyte candidates for the development of all-solid-state batteries (ASSB), owing to the high ionic conductivity exhibited bycloso- andnido-boranes. In this study, an optimised low cost preparation method of MB11H14·(H2O)n, (M = Li and Na) and KB11H14is proposed and analysed. The formation of the B11H14−salt is pH-dependent, and H3O+competes with small ionic radii cations, such as Li+and Na+, to produce a hydronium salt of B11H14−, which forms B11H13OH−upon heating. The use of diethyl ether to extract B11H14−salt from the aqueous medium during synthesis is an important step to avoid hydrolysis of the compound upon drying. The proposed method of synthesis results in LiB11H14and NaB11H14coordinated with water, whereas KB11H14is anhydrous. Hydrated LiB11H14·(H2O)nand NaB11H14·(H2O)nexhibit exceptional ionic conductivities at 25 °C, 1.8 × 10−4S cm−1and 1.1 × 10−3S cm−1, respectively, which represent some of the highest solid-state Li+and Na+conductivities at room temperature. The salts also exhibit oxidative stability of 2.1 Vvs.Li+/Li and 2.6 Vvs.Na+/Na, respectively. KB11H14undergoes a reversible polymorphic structural transition to a metastable phase before decomposing. All synthesisednido-boranes decompose at temperatures greater than 200 °C.